The Evidentiary Role of Visum Et Repertum As Qarinah in Child Rape Cases Under Aceh’s Jinayah Law (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
A person cannot be proven to have committed rape if one of the conditions of proof is not met. This paper aims to reveal the confusion over the non-fulfilment of a primary charge filed by the Public Prosecutor against the defendant in decision No. 17/JN/2016/MS.Mbo at the Meulaboh Syar'iyah Court, and what the scope and proof must certainly be met. This research uses a qualitative method with a type of case study research. Based on the results of this study, it shows interesting facts where a judge rejected the primary charges of the public prosecutor because the evidence could not support the defendant had committed jarimah (offenses against the law) rape. The evidence is in addition to the testimony of witnesses who did not directly see the incident as well as written reports in the form of visum et repertum results in Islamic criminal law referred to as qari ̅nah. In this paper, it will be discovered that the post-mortem or qari ̅nah is part of the judge's ijtihad (effort), and its existence has been recognized by sharia.